The return of Jafar [videorecording (DVD)] - Bennett, Jeff; Shelton, Toby; Stones, Tad; Stones, Tad; Zaslove, Alan; Zaslove, Alan; Alexander, Jason, 1959-; Bettin, Val; Callaway, Liz (Disney DVD., 2005)
The evil Jafar escapes from the magic lamp as an all-powerful genie, ready to plot his revenge against Aladdin.